(3Qhfb GdCdaGX HeYLe GdMaGXs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMajX GdYdje s
(3BNQgG (B:s
(3CKfGA JQLeI CejQ GdeDefjf YeQ Hf GdNWGH s
(3GdfSNI HgG MhGTs
(3Ydi GdfSNI JbQjX HNW GdYdGeI GdcGajjLi GdMfai SfI (B871(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JgPjH h JQJjH s
Keywords: (3GdJGQjNs